Maxwell to Photonics - Couto, M.; Doria, R. (JOURNAL OF ADVANCES IN PHYSICS, 2022)
The main topic to be addressed is the search for a new source of energy: light. Electromagnetism has been the energy that has most changed civilisation in the last two centuries. The emergence of photonics instead of electronics is a new challenge. Photonics is the clean energy to look for. The 20th century was that of electrons. Several innovations took place through electronics. However, despite these numerous innovations due to the electromagnetic properties of the electron, the 21st century will be that of the photon. The advent of a new generation of innovations arising from the electromagnetic properties of the photon is expected. There is a primordial photon from the light invariance still to be revealed, and a growing photonic market awaiting new properties of the photon. The new perspective lies in discovering electromagnetism where the photon is the own source of electromagnetic fields and self-interacting photons at the tree level are generated. Our proposal is the four bosons electromagnetism[1] . A model based on charge transfer. An enlargement to Maxwell supported upon a general electric charge triad {+,0,-} and an extension to gauge symmetry for a nonlinear abelian gauge theory[2] . Elementary particle physics shows several reactions interchanging positive, negative and zero charges. It yields a physicality considering the charges set {+,0,-} mediated by four gauge bosons. A quadruplet physics manifested by photon, massive photon and charged photons. A new EM energy is to be explored. Introducing new electromagnetic sectors beyond Maxwell as nonlinear EM, neutral EM, spintronics, weak interaction, and photonics. The basis for photonic engineering.